EGFR‐targeted Chimeras of Pseudomonas ToxA released into the extracellular milieu by attenuated Salmonella selectively kill tumor cells. Issue 12 (8th July 2016) - Quintero, David; Carrafa, Jamie; Vincent, Lena; Bermudes, David
ABSTRACT: Tumor‐targeted Salmonella VNP20009 preferentially replicate within tumor tissue and partially suppress tumor growth in murine tumor models. These Salmonella have the ability to locally induce apoptosis when they are in direct contact with cancer cells but they lack significant bystander killing, which may correlate with their overall lack of antitumor activity in human clinical studies. In order to compensate for this deficiency without enhancing overall toxicity, we engineered the bacteria to express epidermal growth factor receptor (EGFR)‐targeted cytotoxic proteins that are released into the extracellular milieu. In this study, we demonstrate the ability of the Salmonella strain VNP20009 to produce three different forms of the Pseudomonas exotoxin A (ToxA) chimeric with a tumor growth factor alpha (TGFα) which results in its producing culture supernatants that are cytotoxic and induce apoptosis in EGFR positive cancer cells as measured by the tetrazolium dye reduction, and Rhodamine 123 and JC‐10 mitochondrial depolarization assays. In addition, exchange of the ToxA REDLK endoplasmic reticulum retention signal for KDEL and co‐expression of the ColE3 lysis protein resulted in an overall increased cytotoxicity compared to the wild type toxin. This approach has the potential to significantly enhance the antitumor activity of VNP20009 while maintaining its previously established safety profile. Biotechnol. Bioeng. 2016;113: 2698–2711. © 2016 The Authors. Biotechnology and Bioengineering published by Wiley Periodicals, Inc. Abstract : Tumor‐targeted bacterium VNP20009 expressing the toxin O‐T‐G‐PE38K released into the extracellular milieu selectively kill tumor cells overexpressing the epidermal growth factor receptor (EGFR).